The Sustainability Aspect Affecting the Urban Rainwater Harvesting System in Balikpapan City: A Water Supply Adaption Strategies for The Capital City of Nusantara - Azmanajaya, Emil; Hermansyah, Hadi; Rus, Tatag Yufitra; Kiptiah, Mariatul; Devi, Suheriah Mulia; Aditya, Angga Wahyu; Paulus, Chaterina Agusta (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Water conservation efforts are needed to meet increasing water demand (e.g., rainwater harvesting) to help maintain water and environmental sustainability in the present and future. The interdependence of the five components, which comprised 31 factors, was examined in a quick assessment of urban rainwater harvesting. This study aimed to evaluate the sustainability aspect that affects rainwater harvesting based on five sustainability factors. Stages of the research methodology; 1) Preparation of the research area and respondents, 2) Collecting data through survey methods using interview techniques to obtain related data, 3) Conducting data analysis and characterizing the sustainability of rainwater harvesting, using multi-aspect analysis based on developed factors and attributes, and 4) Using two scenarios reasonably sustainable circumstances urban rainwater harvesting variables, adapting management strategies should be developed based on the urban rainwater harvesting sustainability research, which is in a reasonably sustainable environment. The results show that the sustainability status of urban rainwater harvesting in the City of Balikpapan is relatively consistent, with an indicator of 44.77%. Institutional and technological infrastructure are aspects of low sustainability. To raise sustainability status to 'sustainable,’ then choose scenario number 1, that is a realistic scenario in which the 10 sensitive factors are upgraded, thereby raising the sustainability indicator to 65.52%. The most sensitive attributes to be improved are poor groundwater quality, availability of funding for rainwater harvesting, need for roof cleaning, need for collaboration between stakeholders, and reduction of conflict over taking water sources.